IMPLEMENTASI PROBLEM BASED LEARNING DALAM UPAYA PENINGKATAN KUALITAS PEMBELAJARAN AUDITING - Henny Zurika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research aims to enhance the activity and student learning outcomes through the implementation of problem based on learning as an effort to improve the quality of learning in the course auditing.